Evaluating Capacity Development in Planning, Monitoring, and Evaluation: A case from Agricultural Research - Horton, Douglas; Mackay, Ronald; Andersen, Anders; Dupleich, Luis (International Service for National Agricultural Research, 2000)
This Research Report describes the concepts and methods used to evaluate a regional capacity development project in Latin America. The project under study aims to strengthen planning, monitoring, and evaluation (PM&E) in agricultural research organizations in the region. The report outlines the procedures employed in five evaluation studies and summarizes the results of each study. It then presents consolidated findings in response to three evaluation questions: What were the main contributions of the project to agricultural research management? What lessons can be learned to improve the design of future capacity development programs? What lessons can be learned to improve future evaluations of capacity development?